Descrição osteológica do crânio de um novo dinossauro Prosauropoda do Neotriássico do sul do Brasil - Leal, Luciano Artemio (2001)
ln 1998 a prosauropod skeleton was recovered from the continental Triassic red beds of the Caturrita Formation (Norian), southem Brazil. The specimen (UFSM 11069), housed in the Paleontological Collection of the Universidade Federal de Santa Maria, was coUected in the locality Água Negra, situated close to the town of Santa Maria in the central region, Rio Grande do Sul state. It consists on one of the most complete dinosaurs found in Brazil so far, including a partia! skull and postcranial material. The detailed description of the skull is presented here and an attempt is made to establish the phylogenetic position of this new taxon. The morphological analysis of UFSM 11069, compared with other known forms of the group, has indicated exclusive characters such as the presence of a transversal septum in the fosse of the maxillary medial lamina and a deep depression on the basisphenoid, allowed its classification as a new genus and species in the family Plateosauridae Marsh, 1895. A preliminary phylogenetic valuation, suggests that the UFSM 11069 shares one synapomorphy with Plateosauridae (Coloradisaurus, Sellosaurus, Plateosaurus and Lufengosaurus) which is having a jaw articulation position approxirnately 25% of the length of the tooth row below. It also seems to be more dose related to Coloradisaurus, Sellosaurus and Plateosaurus forming a sister group of this clade supported by two characters which was dentary anterior end in ventral orientation and deep transverse septum between basipterygoid processes. The few numbers of known forms, associated with the importance of the basal dinosaurs as precursors of the great variety reached by the group during the Mesozoic, tum the Triassic dinosaurs extremely important to understand the evolutionary and paleobiogeographic history of these animais.